2007
DOI: 10.1209/0295-5075/80/37002
|View full text |Cite
|
Sign up to set email alerts
|

Charge ordering phase submerged in ferromagnetic ordering phase in the Nd 0.5 Sr 0.5 MnO 3 system

Abstract: In this letter, Nd0.5Sr0.5Mn1- xGaxO3 (0.0⩽x⩽0.075) manganites have been investigated. Diffuse satellite spots and streaks can be seen in transmission electron microscopy and the antiferromagnetic signal in electron spin resonance also occur early at 235 K which is much higher than the usually defined TCO of the Nd0.5Sr0.5Mn1- xGaxO3 sample, indicating that the charge ordering phase already appears in the ferromagnetic regions (TC=250 K). This charge ordering phase is submerged by the ferromagnetic phase so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…The observed anomaly at T co has been reported already [28,29,31] in Nd 1Àx Sr x MnO 3 perovskite materials. The CO phenomenon in Nd 1Àx Sr x MnO 3 perovskite materials has a relatively narrow electron bandwidth [30].…”
Section: Discussionsupporting
confidence: 80%
“…The observed anomaly at T co has been reported already [28,29,31] in Nd 1Àx Sr x MnO 3 perovskite materials. The CO phenomenon in Nd 1Àx Sr x MnO 3 perovskite materials has a relatively narrow electron bandwidth [30].…”
Section: Discussionsupporting
confidence: 80%
“…But in Ga-doped samples, the inflexion in the ρ-T curves can be observed around 240 K for all NSMGO samples, which is shown in the inset of Figure 1(a). In our previous reports, the temperature corresponding to this inflexion is CO temperature T CO [17], while T CO disappears in Cr-doped system. Figure 1(b) shows M-T curves under zero magnetic field cooling (ZFC) and magnetic field cooling (FC).…”
Section: Resultsmentioning
confidence: 67%
“…With decreasing temperature, the peak shifts to a higher field. Our previous work has proved that this peak is derived from the CO phase and also proved that CO phase always exists in Ga-doped samples by ESR spectra [17]. For NSMCO system, in the high temperature above T C , there is a Lorentzian lineshape absorption peak with a Lande factor g ∼2.0.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Some other researchers also reported that the system enters into CO/CE-type antiferromagnetic (AFM) phase at 150 K [1,15,25e34]. But recently, Bo Hong et al reported T CO at 240 K and suggested that the temperature (w150 K) should be defined as T N only [35]. The ground state of NSMO is CO phase with a staggered orbital-order (OO) pattern of d 3xÀr 2 2 and d 3yÀr 2 2 , and CE-type AFM spin [28,33,36] [37].…”
Section: Introductionmentioning
confidence: 99%